PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP, KEHUTANAN DAN PERTANAHAN PROVINSI PAPUA BARAT DAYA - Yeheskel Kambu; Andi Irwan; Mervin Komber (POLITEKNIK LP3I JAKARTA, 2026)
This research aims to analyze the influence of work discipline and work environment on the performance of employees of the Environment, Forestry and Land Service of Southwest Papua Province. This research uses an associative quantitative approach with survey methods. The population and sample in this study amounted to 64 people. Data was collected using a questionnaire and analyzed using multiple linear regression. The research results show that: (1) Work Discipline has a positive and significant effect on employee performance with a sig value of 0.07 < 0.5; (2) The work environment has an effect but is not significant on employee performance with a sig value of 0.105 > 0.5. Simultaneously, both variables have a significant effect on performance